Projective Paternalism - Sandro Ambuehl; B. Douglas Bernheim; Axel Ockenfels (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study experimentally when, why, and how people intervene in others' choices. Choice Architects (CAs) construct opportunity sets containing bundles of time-indexed payments for Choosers. CAs frequently prevent impatient choices despite opportunities to provide advice, believing Choosers benefit. We consider several hypotheses concerning CAs' motives. A conventional behavioral welfarist acts as a correctly informed social planner; a mistakes-projective paternalist removes options she wishes she could reject when choosing for herself; an ideals-projective paternalist seeks to align others' choices with her own aspirations. Ideals-projective paternalism provides the best explanation for interventions in the laboratory and rationalizes support for actual paternalistic policies.
Keywords: D03; D04; H00; 330; paternalism; libertarianism; welfare economics; experiment; false consensus bias